Peran Pendidikan Pancasila dalam pembentukan karakter - Silvia Oktaviana Lestari; Heri Kurnia (Universitas Ahmad Dahlan, 2022)
This article was prepared with the aim of knowing how Pancasila as the basis of the state also has a role in shaping the nation's character. Indonesia can be said to be experiencing a moral and moral crisis, because cases often happen to the community and many of the perpetrators of these cases are still underage. This is certainly something that cannot be underestimated because if it is allowed to continue it will cause the loss of good character in the nation's generation. This article conveys several formulations including: 1) How important is Pancasila Education? 2) What are the values contained in Pancasila? 3) How are Pancasila values applied in shaping character? This study uses a qualitative approach, the method used in compiling this article is a literature study. Sources of data are taken by searching and then reading reference journals. The results of the study show that the application of Pancasila values has a role in shaping character, because in each value of the Pancasila precepts there are goals and ideals of the Indonesian nation. With this Pancasila education, it is hoped that the generation of the Indonesian nation has a character in accordance with the values contained in each item of the Pancasila precepts. The decline in the value of Pancasila as a result of the development of globalization and the development of science can threaten the nation's ideology. Strengthening the values of Pancasila must be carried out to maintain the existing values of Pancasila.